Computed Tomography-Guided Bronchoscopy With an Ultrathin Fiberscope - Kobayashi, Toshiaki (Hindawi Publishing Corporation, 1996)
Bronchoscopy was performed under computed tomography (CT) guidance using an ultrathin fiberscope in a patient with a fluoroscopically invisible lesion that was visualized by CT in the right S(8) and with poor pulmonary function. Under local anesthesia, the ultrathin fiberscope (3 mm in diameter) was inserted close to the lesion (1.5 mm in diameter) under direct visual guidance, and a brush was inserted into the lesion under CT guidance. Cytologic specimens obtained by the brush and washing revealed adenocarcinoma. This is the first report of CT-guided bronchoscopy, which is a new examination method for peripheral small lung lesions and is a less invasive examination than either endoscopic examination with a conventional bronchoscope or open lung biopsy, especially for those with poor pulmonary function.